Jet impingement heat transfer – Part I: Mean and root-mean-square heat transfer and velocity distributions - O’Donovan, Tadhg S.; Murray, Darina B. (International journal of heat and mass transfer, 2007)
Impinging jets provide a means of achieving high heat transfer coefficients both locally and on an area averaged basis. The current work forms the first stage of a two part investigation of heat transfer distributions from a heated flat surface subject to an impinging air jet for Reynolds numbers from 10,000 to 30,000 and non-dimensional surface to jet exit spacing, H/ D, from 0.5 to 8. In the present paper, the relative magnitudes of the local heat transfer coefficients are compared to the fluctuating components and to the mean and root-mean-square local velocity components. It has been shown that at low nozzle to surface spacings (<2 diameters) secondary peaks in the radial heat transfer distributions are due to an abrupt increase in turbulence in the wall jet. In particular the velocity fluctuations normal to the impingement surface have a controlling influence on the enhancement in the wall jet.